2002
DOI: 10.1023/a:1014616113997
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Risk assessment is an essential part of clinical practice. Each of the three aspects of risk (static, stable, and acute dynamic) are important at various points of contact between the man and the systems that are responsible for providing service. Dynamic factors, the typical treatment and supervision targets, have received less research attention than static factors. This paper examined the extent to which pretreatment, posttreatment and change scores were associated with reoffending among men incarcerated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Results indicated that recidivists were more likely to drop out of treatment and display deterioration in their behaviour, whereas the non-recidivists' behaviour generally improved throughout the course of the supervision. Similar results were reported by Hudson, Wales, Bakker, and Ward (2002) whereby sexual reoffenders had more deviant post-treatment scores, and demonstrated less prosocial improvement than non-reoffenders. Similarly, among a sample of general offenders, significant change was noted amid various dynamic risk factors including: employment, leisure time, stress, negative affect, coping, and criminal attitudes (Brown et al, 2009;Jones et al, 2010).…”
Section: Us Draor Validation 10supporting
confidence: 83%
“…Results indicated that recidivists were more likely to drop out of treatment and display deterioration in their behaviour, whereas the non-recidivists' behaviour generally improved throughout the course of the supervision. Similar results were reported by Hudson, Wales, Bakker, and Ward (2002) whereby sexual reoffenders had more deviant post-treatment scores, and demonstrated less prosocial improvement than non-reoffenders. Similarly, among a sample of general offenders, significant change was noted amid various dynamic risk factors including: employment, leisure time, stress, negative affect, coping, and criminal attitudes (Brown et al, 2009;Jones et al, 2010).…”
Section: Us Draor Validation 10supporting
confidence: 83%
“…Rumination over anger provoking situations affects the degree of control an individual has over their anger increasing the risk of re-offending, if not addressed. Research found that rumination over anger was related to sexual recidivism in groups of mixed child molesters (Hudson, Wales, Bakker, & Ward, 2002; Thornton, 2002). Whilst rumination may be well implicated in the risk of recommissioning offences and a growing body of evidence is pointing the central role of negative emotional states in the offence process (Day, 2009), less is known about the role of worry as a mediator between PTSD and risk of re-offending—conceiving worry as a strategy to control perceived threat and to lessen anxiety (Borkovec, Alcaine, & Behar, 2004; Papageorgiou & Wells, 2003; Wells & Sembi, 2004) and as a form of cognitive avoidance which inhibits emotional regulation (Borkovec et al, 2004).…”
Section: Ptsd and Re-offending Risk: Worry And A Negative Perception mentioning
confidence: 99%
“…For example, Nunes and colleagues (2011) found 214 federally incarcerated sex offenders endorsed significantly less rape cognition posttreatment ( d change = 0.75). Although this seems promising, change in rape cognition has been found to be unrelated to sexual recidivism (Beggs & Grace, 2011; Hudson, Wales, Bakker, & Ward, 2002; Nunes, Pettersen, et al, 2016; Olver et al, 2014). For example, Beggs and Grace (2011) found that change in rape cognition was unrelated to sexual recidivism for 202 incarcerated sex offenders.…”
Section: Longitudinal Research On Cognitions Regarding Rapementioning
confidence: 99%